Continuous Quantitative Monitoring of Mural, Platelet-Dependent, Thrombus Kinetics in the Crushed Rat Femoral Vein - Stockmans, F; Deckmyn, H; Gruwez, J; Vermylen, J; Acland, R (Thrombosis and Haemostasis, 1991)
A new in vivo method to study the size and dynamics of a growing mural thrombus was set up in the rat femoral vein. The method uses a standardized crush injury to induce a thrombus, and a newly developed transilluminator combined with digital analysis of video recordings. Thrombi in this model formed rapidly, reaching a maximum size 391 ± 35 sec following injury, after which they degraded with a half-life of 197 ± 31 sec. Histological examination indicated that the thrombi consisted mainly of platelets. The quantitative nature of the transillumination technique was demonstrated by simultaneous measurement of the incorporation of 111In labeled platelets into the thrombus. Thrombus formation, studied at 30 min interval in both femoral veins, showed satisfactory reproducibility overall and within a given animalWith this method we were able to induce a thrombus using a clinically relevant injury and to monitor continuously and reproducibly the kinetics of thrombus formation in a vessel of clinically and surgically relevant size